Enhancing Business Communication Capacity For Small and Medium Enterprises In The Industrial Sector - Hendry Qurniawan; Helfi Nolia; Soni Suharmono; Ujang Permana; Irsan Herlandi Putra (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
In Regency Majalengka, West Java, this community service adopts the idea of business communication training for public perpetrators in Industry Small Intermediate (IKM). The goal of this activity is to increase the public's ability to rise beyond COVID-19 by teaching them more effective communication skills and how to perceive and analyze market trends. At this point, a lot of people are interested in learning about these topics. Method implementation activities take the form of seminars or workshops with around 49 participants over the course of a full day. Outcomes of the action In particular, society has developed the ability to do role-playing, commercial communication, and product interpretation in order to boost income.